Genome-wide association study for lactation characteristics, milk yield and age at first calving in a Thai multibreed dairy cattle population - Yodklaew, Pimchanok; Koonawootrittriron, Skorn; Elzo, Mauricio A.; Suwanasopee, Thanathip; Laodim, Thawee (Agriculture and Natural Resources, 2017)
A genome-wide association study was performed for milk yield per lactation (MY), initial yield (IY), peak yield (PY), persistency (PS) and age at first calving (AFC) in a Thai multibreed dairy cattle population. The dataset contained 1305 first-lactation cows raised on 188 farms located in Central, Northeastern and Southern Thailand. Cows were genotyped with GeneSeek Genomic Profiler low-density bead chips (8810 single nucleotide polymorphism [SNP]; n = 1255) and with high-density bead chips (76,883 SNP; n = 50). The single SNP association analyses utilized 8096 SNPs in common between the low and high density GeneSeek chips. The mixed model contained the fixed effects of contemporary group, fraction of non-Holstein breeds, age at first calving and gene content, and the random effects of animal and residual. Computations were done with the QXPAK.5 software. The number of SNPs associated with MY, IY, PY, PS and AFC at the significant threshold level of p < 0.00001 were 75, 102, 145, 74 and 24, respectively. Of the 366 SNP markers significantly associated with the studied traits, 54 (14.75%) were associated with two traits and 312 (85.25%) with only one trait, and all but one of the 54 SNPs associated with two traits affected MY and lactation characteristics. Genetic improvement of Thai dairy cows for lactation characteristics, milk yield and age at first calving could be aided by selecting animals with the SNP markers found to be highly associated with genes influencing these traits.